The coupling between two heterogeneous InAs quantum dot families and its effect into optical properties. (2nd May 2017) - Das, Debabrata; Panda, Debiprasad; Rawool, Harshal; Chavan, Vinayak; Chakrabarti, Subhananda
Abstract: In this study, we present the coupling between InAs submonolayer (SML) and stranski krastanov (SK) quantum dots (QDs). Interaction between these two different dot families has been manipulated by changing the capping layer thickness. Significant shift in photoluminescence (PL) peak is observed due to the coupling effect. The dynamics of the carriers in this mixed dot matrix has also been modified, which is evident from the increasing activation energy with increasing thickness of the capping layer. Moreover, an ex situ annealing study at different temperatures has been done to check the thermal stability of the as-grown samples. Annealing at lower temperatures, improves the crystal quality a bit, but higher annealing temperatures accelerate the In-Ga interdiffusion and form smaller dots, which is visible from a blue shift in the PL peak of annealed samples. Also, this thermal process improves the dot size distribution.